2020
DOI: 10.1109/access.2020.2980171
|View full text |Cite
|
Sign up to set email alerts
|

Physical Layer Security of Cooperative NOMA for IoT Networks Under I/Q Imbalance

Abstract: In this paper, we investigate the reliability and security of cooperative dual-hop non-orthogonal multiple access (NOMA) for internet-of-thing (IoT) networks, in which the transceivers consider a detrimental factor of in-phase and quadrature-phase imbalance (IQI). The communication between the source and destination is accomplished through a decode-and-forward (DF) relay in the presence of an eavesdropper. In order to characterize the performance of the considered system, exact analytical expressions for the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…During offpeak time, contents are distributed to the small base station and satisfied the requests via edge network at peak time. In our further work, we will study how to insure physical-layer security [45][46][47] or use SE (searchable encryption) [48], [49] for the considered system. In addition, the application of the considered caching strategy in this paper into the IIoT [50], [51] should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…During offpeak time, contents are distributed to the small base station and satisfied the requests via edge network at peak time. In our further work, we will study how to insure physical-layer security [45][46][47] or use SE (searchable encryption) [48], [49] for the considered system. In addition, the application of the considered caching strategy in this paper into the IIoT [50], [51] should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In [20], a relay selection strategy was proposed for multi-hop wireless communication systems having multiple eavesdroppers along with numerous source destination pairs. Considering a relay aided dual-hop communication network, the authors in [21] showed that the intercept probability can be reduced significantly by introducing inphase and quadrature-phase imbalance at the transmitter and receiver nodes. In the above literature [15]- [21], the problem of power allocation has not been addressed.…”
Section: A Related Workmentioning
confidence: 99%
“…[17][18][19][20] In the context of cooperative NOMA, physical layer security has attracted increasing research interests. [21][22][23][24][25][26] In the work of Vo et al, 21 the authors considered imperfect channel state information (CSI) and analyzed the secrecy and throughput of a cooperative NOMA energy harvesting IoT system in the presence of untrust relays. Aimming to against eavesdropping and meanwhile guarantee the quality of service (QoS) of IoTs, a beamforming design was developed by Deng et al 22 for a two-way cognitive radio IoT network.…”
Section: Introductionmentioning
confidence: 99%